2018
DOI: 10.1017/s0022215118001305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of functional and oncological treatment outcomes after transoral robotic surgery and open surgery for supraglottic laryngeal cancer

Abstract: Transoral robotic supraglottic laryngectomy for supraglottic laryngeal cancer is an oncologically safe and functional procedure with better results when compared to conventional open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…It is also of interest when comparing the functional and oncological results of open supraglottic laryngectomy and transoral robotic supraglottic laryngectomy. While there are no differences in overall survival time and disease-specific survival time between groups, the open access operated cohort had a longer oral feeding time, hospitalization and recovery period [ 18 ]. With this knowledge, the goal must be to enable noninvasive surgery for patients who are not treatable by TLM and conventional TORS, such as with the DaVinci System.…”
Section: Discussionmentioning
confidence: 99%
“…It is also of interest when comparing the functional and oncological results of open supraglottic laryngectomy and transoral robotic supraglottic laryngectomy. While there are no differences in overall survival time and disease-specific survival time between groups, the open access operated cohort had a longer oral feeding time, hospitalization and recovery period [ 18 ]. With this knowledge, the goal must be to enable noninvasive surgery for patients who are not treatable by TLM and conventional TORS, such as with the DaVinci System.…”
Section: Discussionmentioning
confidence: 99%
“…Ansarin et al reported an OS of 100% for TORS in T1‐3 supraglottic cancer, although they were also limited by short follow‐up times and a small cohort of 10 patients . Karabulut et al compared TORS to open surgery in supraglottic tumors and found no difference in OS with a mean follow‐up of 26 months . Finally, Kayhan et al reported an OS of 97.9% for TORS in 48 patients with early glottic cancer, and Doazan et al found a 5‐year OS of 78.7% in a multicenter study of 122 supraglottic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased use in laryngeal cancer, there are only a handful of single‐institution studies examining oncologic outcomes following TORS for laryngeal cancer. Those that exist have limited follow‐up, usually <3 years . Furthermore, most of these studies are conducted by high‐volume TORS centers, which creates the potential for publication bias in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent 20 years, the management of advanced larynx cancer underwent a significant evolution, and a gradual shift has been described from operative to nonoperative treatment [ 1 , 3 ]. However, the CRT is associated with several significant side effects, including severe mucositis, pain, and dysphagia [ 4 , 5 ]. Due to the significant toxicity of CRT regimens, there has been a resurgence of interest in the primary surgical management of patients with head and neck cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%